A combination of Deferoxamine mesylate and minimally invasive surgery with hematoma lysis for evacuation of intracerebral hemorrhage. Issue 2 (February 2020) - Pandey, Aditya S; Daou, Badih J; Chaudhary, Neeraj; Xi, Guohua
Intracerebral hemorrhage is associated with significant morbidity and mortality. Some clinical trials demonstrated a trend towards benefit with surgical evacuation of intracerebral hemorrhage, without strong statistically significant results. Subsequent studies focused on minimally invasive techniques. Improved outcomes were more likely with surgical reduction of intracerebral hemorrhage volume to ≤15 mL. Deferoxamine is currently being evaluated as a therapeutic tool in intracerebral hemorrhage with promising results. There continues to be a lack of level I evidence supporting medical and surgical tools for intracerebral hemorrhage evacuation. Could a combination of minimally invasive surgery with hematoma lysis and Deferoxamine result in more effective hematoma evacuation?